A computational study of the microstructural effect on the deformation and fracture of friction stir welded aluminum; Computational Materials Science; Vol. 116 - Balokhonov R. R. Ruslan Revovich; Romanova V. A. Varvara Aleksandrovna; Martynov S. A. Sergey Andreevich; Zinovjev A. V. Aleksandr Valerievich; Zinovieva O. S. Olga Sergeevna; Batukhtin E. E. Ekaterina Evgenjevna (2016, 2016)
Title screen